Molecular Mechanism of Mesenchyme Homeobox 1 in Transforming Growth Factor β1–Induced P311 Gene Transcription in Fibrosis - Wei, Zhiyuan; Han, Chao; Li, Haisheng; He, Weifeng; Zhou, Junyi; Dong, Hui; Wu, Yuzhang; Tian, Yi; Luo, Gaoxing (Frontiers in Molecular Biosciences, 2020)
Organ fibrosis is characterized of excessive fibroblast and extra cellular matrix and the molecular basis are not fully elucidated. Recent studies have proven that P311, an 8-kDa conserved protein, could promote various organ fibrosis, such as skin, kidney, liver, lung, partially through upregulating TGF-β1 translation. However, the upstream regulators and mechanism of P311 gene regulation remains unclear, although we previously found that cytokines, hypoxia and TGF-β1 could upregulate P311 transcription. Here, we aimed to elucidate the molecular mechanism of TGF-β1-induced P311 transcriptional regulation, focusing on Meox1. In this article, we identified the core promoter of P311 through bioinformatic analysis and luciferase reporter assays. Moreover, we demonstrated that Mesenchyme Homeobox 1 (Meox1), induced by transforming growth factor-β1 (TGF-β1), could bind the promoter of P311 and promote its transcriptional activity. Furthermore, the effect of Meox1 on P311 transcriptional expression contributed to altered migration and proliferation in human dermal fibroblast cells. In conclusion, we identified Meox1 as a novel TF of P311 gene, providing a new clue of the pathogenesis in fibrosis.